Un réseau de sources : figures de l’araignée dans Madame Bovary et La Tentation de saint Antoine - Irene Zanot (Flaubert: Revue Critique et Génétique)
An image that has crossed literature since Antiquity, the spider appears in Flaubert’s pages like a leitmotif that recurs in several scenes where it carries major meanings for the artist’s poetics. The author fully exploits the versatility of this animal, which, as Sylvie Ballestra-Puech has shown, acquires a negative value in the Western iconographic and literary tradition. Incarnation of the devil in a production which was inspired by the Bible as well as in some "moralizing" re-readings of the myth of Arachne, an omen of misfortune and madness, this arachnid enters the Flaubertian universe first of all through Ovid’s Metamorphoses. But Flaubert’s spider also feeds on some subterranean works, as demonstrated by the analysis of some passages from Madame Bovary and La Tentation de saint Antoine where the animal is mentioned.